SISTEM EKONOMI SYARI’AH DI SISI KELEMAHAN SISTEM EKONOMI SEKULER DI INDONESIA - Iska, Syukri (El -Hekam, 2019)
Secular economic system is failed and unable to overcome economic problems in Indonesia today. The presence of islamic ecomic system pioneered by the establishment of Islamic financial institutions is expected to be alternative solutions of the problems. Furthermore, this system is expected to bring better atmosphere and prospects as well. This is made possible since the principles of Islamic economic system meets the values of humanity, justice and partnership.